O professor e a pólis: debates discursivos em torno de uma política de inclusão - Miria Gomes de Oliveira (2005)
The dissertation discusses interactive processes between teachers and teacherseducators during weekly pedagogical meetings at municipal schools of Belo Horizonte.Our main aim was to analyze the debates around the proposals and inclusive actions ofthe Pedagogical Project Escola Plural, emphasizing the relation between the teacherand the polis the dimension of the city in which it is discussed its politicalconstruction.Influenced by the reflections of Discourse Analysis and Critical Pedagogy, westarted with the concepts of conflict and consensus, chronotope and the relationsbetween literacy, utopia and schooling to emphasize how the understanding of selfand of ourselves were shown through the teachers speeches.We noticed that the moments of conflict/consensus, caused sometimes by theirinstitutional role and sometimes by ideological divergences, are constitutive part of theprocess of reproduction but also of reevaluation and re-signification of their beliefsabout teacher continuing formation and about school and social justice. These momentsare, therefore, productive because they are the ground of dialogical interactions.We also noticed that the Escola Plural started a historical time hybrid of thespace-time relations that preceded the project as well as of the discourses and ideals ofan Inclusive Critical Pedagogy. The inclusive actions implemented by the projectestablished the discussions around the construction of an inclusive society and openedthe doors for a political debate around literacy practices and around the social role ofschooling.Our data make us believe that an Inclusive Education is an on-going process atthe municipal schools of Belo Horizonte.